Daur Ulang Penggunaan Aspal Panas Retak Kulit Buaya Yang Digunakan Pada Lapis Perkerasan - Tahir, Rizky Hariyanto; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Most of the road construction prosecesses in Indonesia still use convenrional methods, namely using large amounts of aggregate and asphalt, if this is done continuously it use of Reclaimed Asphalt (Cracked Crocodile Skin Asphalt), which is used hot mix material resulting from clod milling exfoliation. This research includes testing the aggregate and Marshall characteristics which were carried out at the Civil Engineering Laboratory Bosowa University. This study aims to determine the characeristics of asphalt mixture (AC-WC) using Reclaimed Asphalt ( Cracked Crocodile Skin Asphalt). As for the addition of new asphalt to Cracked Crocodile Skin Asphalt, namely 1.77%, 2.27%, 2.77%, 3.27%, 3.77% with 1 x 24 hour immersion. This results showed that the addition of new asphalt and immersion would affect the result of the Marshall test.